Hydrodynamical simulations of G2 interpreted as a diffuse gas cloud. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Schartmann, M.; Burkert, A.; Ballone, A.; Alig, C.; Gillessen, S.; Genzel, R.; Eisenhauer, F.; Fritz, T.
Abstract: Recently the gas and dust cloud "G2" was discovered on a highly eccentric orbit around the massive black hole in the Galactic center. The orbit will bring the cloud as close as 2400 Schwarzschild radii to Sgr A* beginning of 2014. With the help of hydrodynamical simulations using the PLUTO code, we investigate possible origins and the fate of the cloud in the coming years. In this proceedings article, we concentrate on a scenario where G2 is interpreted as a diffuse gas cloud and show its detailed evolution in the observable position-velocity diagrams. We further elaborate on the problem of the tail emission which might or might not be related to the G2 cloud.